Risk Factors Affecting Outcome in COVID 19 Patients Admitted in High Dependency Unit, Sir Ganga Ram Hospital Lahore - Shazia Siddique, Amna Omer, Najam-Us-Sehar, Rabia Arshad, Khadeeja Muneeha, Qamar-Uz-Zaman (Pakistan Journal of Medical & Health Sciences, 2022)
Background: COVID-19 is a highly contagious viral infection resulting in severe acute respiratory syndrome Coronavirus (SARS-COV-2). The objective of this study is to determine the risk factors affecting the outcome of moderate to severe COVID 19 patients admitted in HDU of Sir Ganga Ram Hospital, Lahore. Study Design: Prospective cohort study. Place and Duration of Study: COVID HDU of Sir Ganga Ram Hospital, Lahore from 1st June 2020 to 30th November 2020. Methodology: One hundred and eight patients with positive PCR for COVID having moderate to severe COVID disease were enrolled. After written consent, all the demographic and clinical information was obtained. All the patients were followed till their discharge or death. Results: Sixty eight were discharged, 26 were died and14 got left against medical advice. The median age of all patients was53.6 years and the median age of patients who died was significantly older than those who survived. Conclusion: The potential risk factors for high mortality were older age, female sex, those presented with within 1 week from onset of symptoms that need ventilation at admission and comorbidities like Diabetes, Hypertension, and ischemic heart disease. This study could help clinicians to identify patients with poor prognosis at an early stage. Keywords: Covid-19, Outcome, HDU admission criteria